INFLUENCING FACTORS OF DIGITAL CHANNEL USAGE TO SUBSCRIBE INTERNET SERVICE - Imamul Akhyar; Nita Garnida (International Journal of Accounting, Finance and Business, 2021)
In 2020, Pandemic of COVID-19 shocked the world and has been affecting many aspects of life, from economy to lifestyle. People begin to change their habit and adapt to the â€œnew normalâ€ by shifting their routine outside activities into at home internet-based activities, such as online shopping and online learning. This situation becomes the opportunity for internet-based business, including Indihome, an internet service provider in Indonesia, to acquire more customers from digital sales channels. This research is intended to examine factors that influence the usage of digital channels to subscribe Indihome internet services using a modified technology acceptance model (TAM) approach. We applied quantitative online survey to 204 internet users and used structural equation model to measure the relationship among TAM variables. The result showed that perceived ease of use and perceived usefulness significantly and positively influence consumers attitude toward the use of digital channel to subscribe internet service. While level of income significantly influences perceived usefulness of digital channel, we also found that consumersâ€™ perceived access barrier such as confidentiality of personal data and capability does not have significant effect on consumer attitude toward the use of digital channel. Last, as the managerial implication, this study provides key insights for managers to develop digital channel strategy based on research findings.